Optimizing Parathyroid Preservation in Thyroidectomy: The Burjeel Protocol Utilizing Intraoperative Indocyanine Green Near-Infrared Fluorescence Imaging - Iyad Hassan; Lina Hassan; Mohamad Askar; Rawan Khalid Salih (Biomedicines)
Background: Autofluorescence can identify parathyroid glands and protect their vasculature during thyroid surgery to prevent postoperative hypoparathyroidism. This study evaluates the Burjeel intraoperative protocol using near-infrared indocyanine green (ICG-NiR) imaging to preserve parathyroid glands during total thyroidectomy. Methods: This study conducted a single-centre retrospective matched cohort analysis involving 156 consecutive patients who underwent thyroidectomy using the Burjeel ICG-guided near-infrared (NiR) fluorescence protocol (“ICG group”). Patients were matched 1:1 based on gender and extent of resection with 156 counterparts who underwent standard thyroid surgery. The Stryker Spy-phi NiR fluorescence imaging system (Stryker™, Portage, MI, USA) was utilized in three modes—green, black/white, and colourful—to facilitate real-time visualization. Post-lobectomy, each parathyroid gland was individually scored for viability before the closure of the surgical site. Patients were stratified into hypoparathyroidism and euparathyroidism groups based on the parathyroid hormone levels measured on the first postoperative day. Results: The groups had 133 women and 23 men. Preoperative factors like age (43.7 years in both groups); resection time (49 min in the ICG group versus 50 min in the conventional group); and PTH, TPO, and Vit D3 levels were not statistically different. The ICG group had a lower rate of inadvertent parathyroidectomy (9% vs. 17.9% in the standard group, chi-square test, p = 0.015), a lower rate of postoperative hypoparathyroidism (18.6% vs. 35.3%, chi-square test, p = 0.001), and higher postoperative PTH levels (t-test, p = 0.0001). Postoperative hypoparathyroidism was associated with malignant surgical pathology and malignancy on both sides (p = 0.026 and 0.01, respectively). This study found that female participants had a higher incidence of unintentional parathyroidectomy (p = 0.001) but not postoperative hypoparathyroidism. Subgroup analysis showed a negative connection between ICG score and female hypoparathyroidism. Conclusions: The new Burjeel ICG-guided NiR fluorescence approach has greatly reduced inadvertent parathyroidectomy and hypoparathyroidism in female total thyroidectomy patients. Further research is needed to identify numerical variables that aid intraoperative decision-making.